Impact of Covid-19 on the Prevalence of Intrahepatic Cholestasis of Pregnancy - Ruqia Fida, Shakeela Wahab, Asiya Naz, Mustaqeem Shah, Amir Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The virulent pathogen SARS-CoV-2 first appeared in the Chinese province of Hubei in December 2019. Pregnant women were a high-risk population in the pandemic because immune system alterations that occur during pregnancy make them more vulnerable to foreign infections. Late-pregnancy cholestasis is a dangerous liver condition that can cause the foetus to experience potentially fatal problems like early birth and stillbirth. In the present study we were testing the Bile acid level during pregnancy patients after covid pandemic. Objectives: To evaluate the prevalence of intrahepatic cholestasis in pregnant patients after Covid -19 pandemic. Materials and Methods: This cross-sectional study was conducted at department of Dr.fida painless and General Hospital Peshawar from jan 2022 to Dec 2022. We enrolled 186 pregnant patients after fulfilling the inclusion criteria. 5 ml blood sample were also taken from the patients. Serum was extracted and Bile acid test were performed in clinical laboratory. Data were collected in predesign questionnaire. Results: Total 186 patients were enrolled in the study with mean age of 37.18±6.39 years (Range 18-45 years). The mean value of all enrolled patients was 31.38±5.79 with minimum and maximum value of bile acids 20 micromol/L and 40.6.00 micromol/L. In our study 95 (56.5%) of patients belongs to 36 to 45 years of age group followed by age group of 26 to 35 years in which 60 (35.7%) patients and 13 (7.7%) patients were belongs to age group of 18 to 25 years. Practical implication: This study will help the clinical practitioner to take care of pregnant patients in order to avoid the prevalence of intrahepatic cholestasis. Conclusion: It is concluded from this research study that prevalence of intrahepatic cholestasis in pregnancy has increased after Covid-19 pandemic. Keywords: COVID-19, cholestasis, pregnancy, elevated Liver Enzyme, Bile Acids.